Unraveling The Feasibility of Health and Wellness Food Business Through a Financial Perspective : A Case Study of Asa Cerra - Fakhira Elda Khairunnisa; Irawan, Atika (Integrasi Sains Media, 2024)
Asa Cerra is positioning itself to meet the growing global demand for health-conscious and sustainable products. Its flagship offering,